Blended learning en el proceso educativo en los niños y niñas del séptimo año de educación básica en la escuela “Luis Aurelio González” provincia de Bolívar cantón Guaranda en el período lectivo 2021-2022 - Aguirre González, Karla Tatiana (2022)
Knowing that technology is advancing by leaps and bounds, the reasons why educational institutions challenge the change in methodology of the educational process with the new modality of Blended Learning that allows interactive learning, understanding in a better way the knowledge of daily life, taking into consideration that the educational process goes hand in hand with innovative and dynamic technological tools. The focus of our research is qualitative - quantitative whose modality is basic and is supported by a bibliographical, field and social interaction documentary research. The level or type of research is descriptive, the methods used are inductive, deductive, bibliographic, synthetic, logical history, the technique used is a survey of both the teacher and the students, which allowed us to reach the conclusions and thus propose an alternative solution to the problem raised, we worked on the design of an educational guide, taking into account the designs of the graphic interface, information, multimedia, technology and applications necessary for the guide to be easy and understandable. time to use it by teachers and students. The Power Point program is the one we use because of its characteristics, easy to use and allows us to create multimedia applications in a short time. Moreover, it is free software and can be downloaded from the Internet for free.